Financial losses caused by ovine fasciolosis in the Ethiopian highlands - Ngategize, P.K.; Bekele, T.; Tilahun, G. (Springer, 1993)
An estimate of the economic loss due to ovine fasciolosis in the Ethiopian highlands was made based on available data on mortality, weight loss, reduced reproductive efficiency and liver condemnation at slaughhter. The economic effects of fasciolosis were identified and models for estimating the financial loss presented. Ovine fasciolosis losses were estimated at 48.4 million Ethiopian Birr per year of which 46.5, 48.8 and 4.7 percent were due to mortality, productivity (weight loss and reproductive wastage) and liver condemnation, respectively. These losses can be reduced substantially by fasciolosis control programmes that may include the use of anthelmintics, grazing management and nutritional supplementation.